2020
DOI: 10.12659/msm.925491
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptor (P2X7R) of Microglia Mediates Neuroinflammation by Regulating (NOD)-Like Receptor Protein 3 (NLRP3) Inflammasome-Dependent Inflammation After Spinal Cord Injury

Abstract: Background Microglia participate in mediating neuroinflammation in which P2X7R triggered by adenosine triphosphate has a critical effect after spinal cord injury. However, how the P2X7R of microglia regulate neuroinflammation after spinal cord injury is still unclear. The aim of this study was to explore the mechanism by which the P2X7 receptor of microglia regulates neuroinflammation after spinal cord injury in NLRP3 inflammasome-dependent inflammation. Material/Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Alternatively, these inhibitory neurotransmitters could also reduce the release of neuronal excitatory neurotransmitters, such as glutamate and ATP, which in turn decrease glial cell activity indirectly ( 44 ). Specifically, it has been demonstrated that P2X purinoceptor 7 (P2X7) and P2X4 are expressed on microglia ( 45 , 46 ). Once these purinergic receptors are activated by ATP, the MAPK pathway (including p38) is phosphorylated, and the downstream pro-inflammatory mediators IL-1β and TNF-α are synthesized and influence neurons to perpetuate the nociceptive response.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, these inhibitory neurotransmitters could also reduce the release of neuronal excitatory neurotransmitters, such as glutamate and ATP, which in turn decrease glial cell activity indirectly ( 44 ). Specifically, it has been demonstrated that P2X purinoceptor 7 (P2X7) and P2X4 are expressed on microglia ( 45 , 46 ). Once these purinergic receptors are activated by ATP, the MAPK pathway (including p38) is phosphorylated, and the downstream pro-inflammatory mediators IL-1β and TNF-α are synthesized and influence neurons to perpetuate the nociceptive response.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence that neuro-glial communication is affected by upregulation of glial purinergic receptors in neurodegeneration. For instance, microglial upregulated P2X7 (184)(185)(186) leads to an exacerbation of a pro-inflammatory microglial phenotype and increased release of proinflammatory molecules, which disrupt synaptic communication (187)(188)(189). Pro-inflammatory molecules like chemokines or reactive oxygen species also affect oligodendrocytes and astrocytes, causing oligodendrocyte cell death (190)(191)(192) and astrocytic reactivity (6), leading to further cell and network impairment.…”
Section: Purinergic Signaling Crosstalk In Neurodegenerationmentioning
confidence: 99%
“…Moreover, the in vivo results demonstrated that CY-09 regressed the xenografted tumor growth of osteosarcoma. The therapeutic value of CY-09 has been mainly reported in inflammatory diseases, including inflammation after spinal cord injuries Fan et al (2020) and cerebral ischemia/reperfusion injuries ( Sun et al, 2020 ). Recently, researchers also focused on contributing chronic inflammation created by NLRP3 activation to carcinogenesis, including proliferation, angiogenesis, immunosuppression, and metastasis Liu et al (2021) , Huang et al (2017) , and Chen et al (2018) showed that blockage of the NLRP3 inflammasome could enhance the antitumor immune responses in head and neck squamous cell carcinoma, suggesting that the NLRP3 inflammasome pathway may be regarded as a novel approach for the treatment of head and neck squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%